The secret life flowers - Jensen, Lawrence; Chung, Andrew (New Zealand : ETI ; Dr. Lawrence Jensen, 2000)
Three dimensional animations take you inside both structures to see sporangia and gametophytes. Dynamic events such as pollination, gametophyte formation, fertilisation, embryo formation and fruit formation are seen as spectacular computer simulations
Title from title screen
Editors, Andrew Chung, Richard Smith ; animation, Andrew Chung ; camera, Graeme Henderson, Richard Smith
Narrator: Richard Smith
Keywords: Flowers -- Anatomy; Flowers